A comprehensive panel data analysis on the empirical financial performance of Islamic banking in Malaysia - Al-Shaghdari, Fahd Mohammed Obad; Saeid Ibrahim, Kamal Mustafa; Muhammad, Tijjani (Springer Nature Switzerland, 2025)
The objective of this study is to quantitatively assess the financial perfor mance of Islamic banks in Malaysia. This study applies a quantitative research methodology using random effects models using GLS regression via Stata soft ware, which was developed on panel data collected for a 10-year period from a data stream database on a yearly basis for 15 Islamic banks based in Malaysia from 2013 to 2022. This study employs ROAA as a proxy for financial performance measure ment, and the data encompasses a panel dataset for fully established and subsidiary Islamic banks in Malaysia. The findings elucidate a discernible and favorable corre lation between the financial performance of Islamic banks and both liquidity and interest rates. Nevertheless, factors such as asset quality, bank size, inflation, tax rate, and GDP growth rate were found to be inconsequential in exerting influence on the financial performance of Islamic banks. As a result, it is anticipated that this research will lay a solid foundation on which academics and scholars can build to gain a deeper understanding of Islamic banking in Malaysia and other different countries and regions. The results show the massive growth and latest assessments of Islamic banks and their performance, exempting non-compliant elements from influencing the financial performance of Islamic banks. Therefore, it contributes the most to management, policymakers, and businesses in Malaysia.